2019
DOI: 10.5194/bg-2018-528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humic surface waters of frozen peat bogs (permafrost zone) are highly resistant to bio- and photodegradation

Abstract: <p><strong>Abstract.</strong> Bio- and photo-degradation of dissolved organic matter (DOM) is identified as dominant vector of C cycle in boreal and high-latitude surface waters. In contrast to large number of studies of humic waters from permafrost-free regions and oligotrophic waters from permafrost-bearing regions, the bio- and photo-lability of DOM from humic surface waters of permafrost-bearing regions has not been thoroughly evaluated. Following standardized meth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…DOC concentrations in studied waterbodies were quite high (median 60–20 mg L −1 for different size bins, and decreasing with lake size) and exceeded values observed in soil pore waters of wetlands in the southern part of the studied territory (20–30 mg L −1 ; Avagyan et al 2014). Also, given the likely short residence time of water in these small thaw ponds and depressions (Manasypov et al 2015), this DOC input from the peat soil would be quickly replenished as well as rapidly bio‐ and photodegraded as was recently suggested for small waterbodies of eastern European tundra (Shirokova et al 2019). The very low quality of DOC that remains after fast initial degradation of DOM in waterbodies of the BZT is confirmed by the high values of SUVA 254 (from 3 to 6 L mg − 1 m −1 ) which was independent of the season and size of the waterbody (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 79%
“…DOC concentrations in studied waterbodies were quite high (median 60–20 mg L −1 for different size bins, and decreasing with lake size) and exceeded values observed in soil pore waters of wetlands in the southern part of the studied territory (20–30 mg L −1 ; Avagyan et al 2014). Also, given the likely short residence time of water in these small thaw ponds and depressions (Manasypov et al 2015), this DOC input from the peat soil would be quickly replenished as well as rapidly bio‐ and photodegraded as was recently suggested for small waterbodies of eastern European tundra (Shirokova et al 2019). The very low quality of DOC that remains after fast initial degradation of DOM in waterbodies of the BZT is confirmed by the high values of SUVA 254 (from 3 to 6 L mg − 1 m −1 ) which was independent of the season and size of the waterbody (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Although dissolved iron was not reported (Stubbins et al, 2016), dilution likely also resulted in the precipitation of iron (oxy)hydroxides and thus lower dissolved iron concentrations (Miller et al, 2009). In a study of Russian arctic surface waters that likely contained permafrost DOC (Shirokova et al, 2019), up to 13% of the DOC pool was photomineralized to CO 2 , consistent with the presence of dissolved iron (3–7 μM). Provided that all permafrost DOC contains carboxyl C (Feng et al, 2017; Ward et al, 2017; Ward & Cory, 2016) and that permafrost soils generally contain high levels of leachable iron (Herndon et al, 2015; Heslop et al, 2019; Ping et al, 1998; Trusiak et al, 2019), arctic permafrost DOC is labile to photomineralization in proportion to the iron present.…”
Section: Resultsmentioning
confidence: 88%
“…The presence of iron may explain contrasting literature results from high (Selvam et al, 2017; Shirokova et al, 2019; Ward & Cory, 2016) to little or no (Shirokova et al, 2019; Stubbins et al, 2016) lability of permafrost DOC to photomineralization. For example, undetectable photomineralization of permafrost DOC from Russian arctic thaw slumps (Stubbins et al, 2016) may have been due to the 100‐fold dilution of the DOC with deionized water.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, incubations of High Arctic pond DOM to sunlight also revealed the absence of significant loss in dissolved organic carbon (DOC) over a few days, but a rapid loss of color and the cleavage of large molecules into smaller moieties (Laurion and Mladenov 2013). Humic waters from frozen peat bogs in Siberia were shown to be resistant to both photochemical and microbial mineralization (Shirokova et al 2019), and low biolability of permafrost soil organic matter has been recently reported (Kuhry et al 2020). Much still remains to be understood regarding the combined effects of microbial and sunlight degradation processes on DOM mineralization in Arctic freshwaters.…”
mentioning
confidence: 99%